(untitled) - Glendinning, Eric H. (Cambridge, 2004)
This book for intermediate and above students includes authentic texts from textbooks, journals, reference works and study guides. Study Reading is a course for learners of intermediate level or above who need to develop their reading skills for study or work purposes. The book is divided into three parts. Part 1 introduces basic reading skills. Part 2 is theme based, with texts from a variety of disciplines, and aims to extend the skills introduced in Part 1. Part 3 covers the reading skills required for project, dissertation and thesis work. Study Reading encourages learners to reflect on their current reading strategies. By doing a variety of task-based, problem-solving activities, learners are encouraged to refine their reading strategies through exposure to the ideas of others. The book also gives direct advice on how to improve reading efficiency. Study Reading is part of a series, Study Writing, Study Listening, Study Speaking, Study Skills. Second Editions of Study Speaking, Listening and Skills will appear at the same time as the Second Edition of Study Reading. The Second Edition of Study Writing will appear in late 2005. Study Reading: - adopts a learner centred approach suitable for both classroom use and self-study. - has clearly labelled sections which allow users to select and focus on the skills areas most appropriate to their needs. - includes authentic texts from textbooks, journals, reference works and study guides currently used in universities, colleges, and other institutions of higher learning. - can also be used by students working on their own. The book contains a detailed answer key. The Second Edition has been updated to include not only more recent texts in the disciplines represented but also to take account of new media with the growth of on-line resources. For the first time, too activities are included for IELTS practice.
Keywords: Reading (Higher education),English language; Study and teaching (Higher),Foreign speakers